Lignocellulosic biofuel: a way forward - Abd. Aziz, Suraini (Universiti Putra Malaysia Press, 2014)
Economic dependency on fossil fuels and the resulting effects of its usage on the environment has placed considerable focus on utilizing biosugars from lignocellulosic biomass, the largest known renewable carbohydrate source as an alternative. Biosugars are derived from cellulose and hemicelluloses constituents; however these are in turn not readily accessible to enzymatic hydrolysis and hence requiring pretreatment, for extensive modification of the lignocellulosic structure. A number of pretreatment technologies are currently under development and tested at pilot scale. Hydrolysis of lignocellulose into biosugars requires a number of different cellulases and hemicellulases. The hydrolysis by cellulases is a sequential breakdown of the linear glucose chains, whereas hemicellulases must be capable of hydrolysing branched chains containing different sugars and functional groups. The technology for pretreatment and hydrolysis has been developed to an extent that is close to a commercially viable level. For example, processing of lignocelluloses at high substrate levels have become possible, all the while with improvements made on enzyme performances. In addition, the cost of enzymes has also been reduced. Nevertheless, a number of technical and scientific issues within pretreatment and hydrolysis remain to be solved and with significant expected improvements in yield and cost reductions, large-scale fermentation of lignocellulosic biomass is conceived to be possible. The concept of producing lignocellulosic biofuel, bioproducts and chemical through a biorefinery using lignocellulosic biomass had been around for 70 years or more. The use of renewable energy resources has become essential at a time when the focus is on global warming, carbon dioxide emission, security of energy supply, and reduction in consumption of fossil-based fuels. The recent interest in this biorefinery concept is based on the mitigation of climate change by substituting the biomass energy for petroleum or other fossil-fuel energy. Thus the realization of biorefinery concept remains a challenge.